Requirement for A-type cyclin-dependent kinase and cyclins for the terminal division in the stomatal lineage of Arabidopsis - Yang, Kezhen (Journal of experimental botany, 2014)
© The Author 2014. Published by Oxford University Press on behalf of the Society for Experimental Biology.